The Employment Precariousness Scale (EPRES): psychometric properties of a new tool for epidemiological studies among waged and salaried workers - Vives Vergara, Alejandra (2010)
Fil: Vives Vergara, Alejandra. Universitat Pompeu Fabra. Department of Political and Social Sciences; España. Comisión Nacional de Investigación Científica y Tecnológica. Fondo de Financiamiento de Centros de Investigación en ?reas Prioritarias. Pontificia Universidad Católica de Chile. Escuela de Medicina. Departamento de Salud Pública; Chile